KOMBINASI PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNGA KOL - Agung Dwi Arnanto; Anis Rosyidah; Anis Sholihah (AGRONISMA, 2021)
This study aims to determine the effect of a combination of organic and inorganic goat manure on the growth and yield of cauliflower. The study used a Randomized Block Design (RAK) consisting of 7 types of combinations, namely: Control = Without using Urea and Goat Manure, N1 = 100% Urea, N2 = 50% Urea + 50% ZA, N3 = 75% Urea + 25% Goat Manure, N4 = 50% Urea + 50% Goat Manure, N5 = 25% Urea + 75% Goat Manure and N6 = 100% Goat Manure. Parameters observed were plant height, number of leaves, fresh weight of crop, fresh weight of roots, total fresh weight of plants, crop diameter, marketable weight, root dry weight, crop dry weight, total plant dry weight and total dissolved solids. The results showed that the combination of organic and inorganic fertilizers in the N5 treatment (25% urea + 75% goat manure) gave the best results on the growth and yield of cauliflower.